Problematic BPJS health patient pending claims in the implementation of INA-CBGS and management handling - Sulastri Sulastri; Menap Menap; Sastrawan Sastrawan (Institute of Computer Science (IOCS), 2023)
Guarantee program health (BPJS Health ) does payment to facility health reference level continued (FKRTL) in Indonesian Case Base Groups (INA-CBGs). BPJS health claim is submission cost maintenance patient participant guarantee health national (JKN) by parties House Sick to BPJS health carried out _ in a way collective and billable every the month . Currently _ Still happen problem between BPJS Health and Advanced Level Referral Health Facilities (FKRTL) including the relevant Bima City Hospital with problem coding that doesn't appropriate , medical resumes are not complete , incomplete relevant between medical resumes with results inspection support medical , and errors entry claim . Research objectives This is For know in a way deep regarding : (1) System planning management claim ; (2) System organizing ; (3) Implementation management record medical and files condition claim ; (4) System supervision in management JKN claim . Study This use approach studies case . Research results : (1) SPM recording has not been implemented medical ; (2) The hospital's internal coders and verifiers are not yet available equipped knowledge knowledge INA-CBGs coding , internal verification still underway done manually because _ Not yet There is application internal verification ; (3) Implementation management record medical and files condition claim Not yet in accordance with PMK number 26 of 2021 and BA agreement together guide management solution problem INA-CBGs claims in 2020; (4) System supervision in management JKN claim yet held optimally.